2011
DOI: 10.4061/2011/290853
|View full text |Cite
|
Sign up to set email alerts
|

A Morphological Approach to the Diagnosis of Protozoal Infections of the Central Nervous System

Abstract: Protozoal infections, though endemic to certain regions, can be seen all around the world, because of the increase in travel and migration. In addition, immunosuppression associated with various conditions, particularly with HIV infection, favors the occurrence of more severe manifestations and failure to respond to treatments. The CNS may be the only affected system; when not, it is often the most severely affected. Despite information obtained from clinical, laboratory, and imaging procedures that help to na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 51 publications
0
11
0
2
Order By: Relevance
“…At least, some evidence in line with the importance of T. brucei phagocytosis by microglia alluded in this study have been reported. In post-mortem samples of patients with African trypanosomiasis the presence of diffuse meningoencephalitis, diffuse microglial hyperplasia, proliferation of large astrocytes, and formation of microglial nodules was described by immunohistochemical observations 44 , 45 . Therefore, this study stresses the importance and opens up new avenues for understanding the cellular function of microglial cells in the meningoencephalitic stage of HAT.…”
Section: Discussionmentioning
confidence: 99%
“…At least, some evidence in line with the importance of T. brucei phagocytosis by microglia alluded in this study have been reported. In post-mortem samples of patients with African trypanosomiasis the presence of diffuse meningoencephalitis, diffuse microglial hyperplasia, proliferation of large astrocytes, and formation of microglial nodules was described by immunohistochemical observations 44 , 45 . Therefore, this study stresses the importance and opens up new avenues for understanding the cellular function of microglial cells in the meningoencephalitic stage of HAT.…”
Section: Discussionmentioning
confidence: 99%
“…Estudios de series de casos estudiados con autopsias indican que la enfermedad de Chagas cerebral tiene compromiso de la materia gris y blanca, pero predominantemente en ésta última, se localizan en varios lóbulos cerebrales donde alcanzan su mayor tamaño y también se ubican en el cerebelo y tronco cerebral, pero sin compromiso de los ganglios basales. En contraste, los pacientes con toxoplasmosis cerebral, tiene compromiso de corteza cerebral o sustancia blanca pero a nivel subcortical y casi todos presentan compromiso de los ganglios basales 19,20 . Sin embargo, en ocasiones los pacientes con toxoplasmosis cerebral pueden presentar lesiones infratentoriales 20 .…”
Section: Discussionunclassified
“…En contraste, los pacientes con toxoplasmosis cerebral, tiene compromiso de corteza cerebral o sustancia blanca pero a nivel subcortical y casi todos presentan compromiso de los ganglios basales 19,20 . Sin embargo, en ocasiones los pacientes con toxoplasmosis cerebral pueden presentar lesiones infratentoriales 20 . La evolución de las imágenes en nuestro paciente fue confirmando este patrón con compromiso supra e infratentorial, cerebeloso y de tronco sin afectar los ganglios basales.…”
Section: Discussionunclassified
“…Infectious diseases continue to represent leading causes of the global burden at social, economic, and public health levels [1][2][3][4]. Several parasite-borne infectious diseases are especially threatening because of their global impact, including malaria, leishmaniases, and toxoplasmosis.…”
Section: Introductionmentioning
confidence: 99%